Quality of Work Life and Work Motivation on Employee Performance with Job Satisfaction as Moderating Variable - Fitria, Fitria; surajiyo, surajiyo; Ronal Aprianto; Irma Idayati; Hardi Mulyono; Rindi Ningmas (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
This study aims to determine the effect of Quality of Work Life and Work Motivation on Employee Performance with Job Satisfaction as a Moderating Variable at the Agriculture Office of Lubuklinggau City. The research method used in this study is a quantitative method. Quantitative methods can be defined as research methods based on the philosophy of positivism, used to examine certain populations or samples, collecting data using research instruments, analyzing quantitative/statistical data with the aim of testing predetermined hypotheses. Data collection techniques were carried out by means of observation, interviews and documentation. The results of the study indicate that there is an indirect effect of work motivation on employee performance through job satisfaction as a moderating variable at the Lubuklinggau City Agriculture Service, this is based on the results of the indirect effect value for the influence of work motivation on performance through job satisfaction as a moderating variable of 0.143 with a t-value the statistic of 2254 is greater than the t-table value of 1.96. significance value of 0.025. Furthermore, there is an indirect effect on the quality of work life on performance through job satisfaction as a moderating variable at the Lubuklinggau City Agriculture Service, this is based on the results of the indirect effect value for the influence of the quality of work life on performance through job satisfaction as a moderating variable of 0.274 with a t-statistic value of 4.167 is greater than the t-table value of 1.96. significance value of 0.000. It can be concluded that the quality of work life and work motivation affect employee performance with job satisfaction as a moderating variable at the Lubuklinggau City Agriculture Office. and there is an indirect effect of the variables of Quality of Work Life and Work Motivation have an effect on Employee Performance with Job Satisfaction as a Moderating Variable in the Agriculture Service of Lubuklinggau City.